Chromatin features of plant telomeric sequences at terminal vs. internal positions - Majerová, Eva; Mandáková, Terezie; Vu, Giang T. H.; Fajkus, Jiří; Lysak, Martin A.; Fojtová, Miloslava (Frontiers in Plant Science, 2014)
Epigenetic mechanisms are involved in regulation of crucial cellular processes in eukaryotic organisms. Data on the epigenetic features of plant telomeres and their epigenetic regulation were published mostly for Arabidopsis thaliana, in which the presence of interstitial telomeric repeats (ITRs) may interfere with genuine telomeres in most analyses. Here, we studied the epigenetic landscape and transcription of telomeres and ITRs in Nicotiana tabacum with long telomeres and no detectable ITRs, and in Ballantinia antipoda with large blocks of pericentromeric ITRs and relatively short telomeres. Chromatin of genuine telomeres displayed heterochromatic as well as euchromatic marks, while ITRs were just heterochromatic. Methylated cytosines were present at telomeres and ITRs, but showed a bias with more methylation towards distal telomere positions and different blocks of B. antipoda ITRs methylated to different levels. Telomeric transcripts TERRA (G-rich) and ARRET (C-rich) were identified in both plants and their levels varied among tissues with a maximum in blossoms. Plants with substantially different proportions of internally and terminally located telomeric repeats are instrumental in clarifying the chromatin status of telomeric repeats at distinct chromosome locations.